2018
DOI: 10.1111/trf.14510
|View full text |Cite
|
Sign up to set email alerts
|

Soluble antigens in plasma allow mismatched transfusion without hemolysis

Abstract: Our study shows that secretor status would provide protection from isoantibodies. The dissolved B antigens in the group B plasma absorb and/or bind to the group B isoantibodies in the group A plasma. This mechanism gives a protective effect against hemolytic reactions in massive transfusion situations in the trauma setting when group A plasma is used instead of group AB plasma. This protective effect is revealed with the paucity of intravascular hemolysis observed in these out-of-group massive transfusions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
10
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 17 publications
0
10
0
Order By: Relevance
“…These transfused group O RBCs reduce the volume of the autologous RBCs that could be susceptible to hemolysis from group A plasma. Second, 80% of group B and AB recipients (i.e., those who are potentially susceptible to hemolysis from group A plasma) will be secretors of soluble B substance that would neutralize the anti‐B present in the group A thawed plasma . Third, the experience from the transfusion of minor mismatched platelets (PLTs) has demonstrated that hemolysis from group A PLTs is uncommon .…”
mentioning
confidence: 99%
“…These transfused group O RBCs reduce the volume of the autologous RBCs that could be susceptible to hemolysis from group A plasma. Second, 80% of group B and AB recipients (i.e., those who are potentially susceptible to hemolysis from group A plasma) will be secretors of soluble B substance that would neutralize the anti‐B present in the group A thawed plasma . Third, the experience from the transfusion of minor mismatched platelets (PLTs) has demonstrated that hemolysis from group A PLTs is uncommon .…”
mentioning
confidence: 99%
“…Although ABO‐incompatible platelet and plasma transfusions both result in the transfusion of anti‐A and/or anti‐B antibodies, concern for clinically significant hemolysis in the transfusion recipient is low. This is due to several protective factors, including the presence of A and B antigen on endothelial cells, dilution of transfused plasma into the patient blood volume, and soluble A and B antigen in the plasma of secretors . All of these factors serve to decrease risk for hemolysis of recipient red cells.…”
Section: Issue #1: Abo Compatibilitymentioning
confidence: 99%
“…However, higher titers do not guarantee hemolysis in the incompatible recipient as reported from one center where 26% of group O apheresis platelets had anti‐A and/or anti‐B IgG titers > 256 and almost 10% had titers > 512 without evidence of hemolysis . Variables such as antibody subclass and soluble ABH antigens that exist in approximately 80% of the population may help explain why hemolysis is a rare complication of incompatible plasma transfusion . The absolute amount of incompatible anti‐A and anti‐B that can be safely transfused to recipients has yet to be defined.…”
Section: Issue #1: Abo Compatibilitymentioning
confidence: 99%
See 2 more Smart Citations